C3-Selective alkenylation of N-acylindoles with unactivated internal alkynes by cooperative nickel/aluminium catalysis. Issue 32 (6th April 2017) - Inoue, Fumiyoshi; Saito, Teruhiko; Semba, Kazuhiko; Nakao, Yoshiaki
Abstract : Highly regio- and stereoselective alkenylation of N -acylindoles with unactivated internal alkynes has been accomplished by cooperative nickel/aluminium catalysis to afford C3-alkenylated indoles. Abstract : Highly regio- and stereoselective alkenylation of N -acylindoles with unactivated internal alkynes has been accomplished by cooperative nickel/aluminium catalysis to afford C3-alkenylated indoles. Coordination of the acyl moiety to a bulky aluminium-based Lewis acid plays a crucial role in the selective functionalization at the C3-position by electron-rich nickel(0) catalysis.